Trends in working conditions and health across three cohorts of older workers in 1993, 2003 and 2013: a cross-sequential study - M. van der Noordt; H. J. Hordijk; W. IJzelenberg; T. G. van Tilburg; S. van der Pas; D. J. H. Deeg (BMC, 2019)
Abstract Background Over the past decades, the number of older workers has increased tremendously. This study examines trends from 1993 to 2013 in physical, cognitive and psychological functioning among three successive cohorts of Dutch older workers. The contribution of the changes in physical and psychosocial work demands and psychosocial work resources to change in functioning is examined. Insight in health of the older working population, and in potential explanatory variables, is relevant in order to reach sustainable employability. Methods Data from three cohorts (observations in 1993, 2003 and 2013) of the Longitudinal Aging Study Amsterdam (LASA) were used. Individuals aged 55-65 with a paid job were included (N = 1307). Physical functioning was measured using the Timed Chair Stand Test, cognitive functioning by a Coding Task and psychological functioning by the positive affect scale from the CES-D. Working conditions were deduced from a general population job exposure matrix. Linear and logistic regression analyses were performed. Results From 1993 to 2013, time needed to perform the Timed Chair Stand Test increased with 1.3 s (95%CI = 0.89-1.71), to a mean of 11.5 s. Coding Task scores increased with 1.7 points (95%CI = 0.81-2.59), to a mean of 31 points. The proportion of workers with low positive affect increased non-significantly from 15 to 20% (p = 0.088). Only the improvement in cognitive functioning was associated with the change in working conditions. The observed decrease of physically demanding jobs and increase of jobs with higher psychosocial resources explained 8% of the improvement. Conclusions Changes in working conditions may not contribute to improved physical and psychological functioning, but do contribute to improved cognitive functioning to some extent. Further adjustment of physical work demands and psychosocial work resources may help to reach sustainable employability of older workers.